Holotypes of ostracods of Order Podocopida from the collection of the Museum of A.V.Zhirmunsky Institute of Marine Biology FEB RAS (Vladivostok) - Schornikov, Evgeny I.; Tsareva, Olga A. (Zootaxa, 2009)
The Museum collection of A.V. Zhimunsky Institute of Marine Biology FEB RAS contains 208 holotypes of ostracods of Order Podocopida described in 25 works of E.I. Schornikov and co-authors published within the period of 1969–2006. The list of these holotypes includes taxa of suprageneric level listed in systematic order, and taxa of lower level are listed in alphabetic order. New numbers, assigned to the holotypes instead of the previous ones as the result of reorganization of the Museum specimen collections, are supplied, as well as revised and modern names if the original ones were changed, and corresponding references.